Emulgel Formulation And Evaluation Utilizing Natural Polymer For Antifungal Activity - Vazir, Alina; Teotia, Deepak (Journal of Neonatal Surgery, 2025)
Emulgel is a brand-new, innovative topical medication delivery technology that combines the benefits of hydrophilic gel and emulsions.Emulgel comprises both emulsions entrapped in polymer gel phase. To comprehend the drug and its behavior, preformulation research is carried out. Preformulation research included drug identification via DSC, FTIR, melting point, and solubility. To facilitate further drug calculations, a calibration curve for fluconazole in ethanol and pH 5.5 phosphate buffer is developed. Two approaches were used in the drug excipient compatibility investigation. Drug and drug excipient physical stability tests are conducted at room temperature and run for 14 and 28 days, respectively. The FTIR technique was used to verify the medication and polymer compatibility. The carbomer polymer and fluconazole are compatible. For the creation of emulgel, carbomer homopolymer type C and aloevera are utilized. Aloevera demonstrated exceptional gelling qualities. Physical characteristics, rheological investigations, pH of the formulations, texture analyzer spreadability, bioadhesive strength assessment, extendability, drug content determination, and invitro drug release tests are all considered when evaluating formulations. The chosen formulation is stable for one month and was charged for the stability research at rapid, intermediate, and room temperature storage settings.